IMPLEMENTASI E-MARKETING MELALUI SOSIAL MEDIA INSTAGRAM DAN KUALITAS PRODUK UNTUK MENINGKATKAN KEPUTUSAN PEMBELIAN DI SECANGKIR TEMU CAFÉ BANDUNG - Wardani, Yudha; Fernandajaya, Erik; Fitriyani, Ratikah (Puslitabmas Batam Tourism Polytecnic, 2024)
This research aims to understand the impact of e-marketing strategies and perceptions of product quality on consumer purchasing decisions in the coffee industry, particularly focusing on coffee establishments in Bandung. Utilizing a quantitative research method, the study collects data from respondents acting as visitors at one of the cafes that offers coffee, namely Secangkir Temu. Statistical analysis will be used to evaluate the extent to which e-marketing strategies and product quality interact and influence purchasing decisions. The results of this research are expected to provide guidance for restaurant operators, especially those themed around coffee in the coffee industry, to optimize their digital marketing strategies and improve product quality, thereby strengthening consumer appeal and increasing levels of purchase satisfaction and athmosfhere.